Evaluasi Efek Samping Obat Anti Tuberkulosis (Oat) Pasien Tuberkolusis Paru Dewasa Di Rumah Sakit Imanuel Bandar Lampung - Putri, Tiara Aprilia; Primadiamanti, Annisa; Angin, Martianus Perangin (Jurnal Ilmiah Wahana Pendidikan, 2025)
Based on data from the Lampung Provincial Health Office in 2019, the highest TB case finding was in Bandar Lampung City (2,050 male cases, 1,435 female cases, and 361 cases in children aged 0-14 years). Based on the condition of TB treatment which has a long duration of drug administration and many types of drugs, there will be a high risk of side effects or toxicity. This study is a quantitative study using an analytical survey design. The study and data collection were conducted at the Imanuel Hospital, Bandar Lampung in April 2024. The population in this study were all adult TB patients at the Imanuel Hospital, Bandar Lampung, in the period January - March 2024, totaling 31 pasients. The instrument used was a direct observation sheet. Analysis of ESO events using presented in a peer review. Based on the results of monitoring pulmonary TB patients at the Imanuel Hospital, Bandar Lampung City, it can be concluded that the proportion of patients who experience the most side effects of OAT is joint pain. Other side effects that are often experienced by TB patients are nausea, loss of appetite, dizziness and tingling